ELEMENTS OF THE COGNITIVE ANALYSIS OF PUBLIC POLICIES IN THE UNDERSTANDING OF SCHOOLING ACTIONS IN DIFFERENT TERRITORIES AND THEIR TERRITORIALITIES - Pupimperdonatti, Vera Maria [UNESP]; Lemes, Sebastiao De Souza [UNESP] (Unesp-faculdade Ciencias & Letras, 2022)
This work intends to present discussions related to the foundations of cognitive analysis of public policies through a conceptual theoretical framework that includes decisions, instrumentation and regulation that reverberate in the complexity of schooling in Brazil and, in a second place, based on such reflections, conceptualize the scholar institution and schooling in the context of territoriality. In view of the considerations presented based on a qualitative perspective, and with the purpose of reflecting on the bases of cognitive analysis of public policies, considerations about Brazilian education are addressed, aiming at a contextualized understanding of the concepts of cognitive or normative matrices; the action of public actors and public agents toward education policies; public policy instruments and modes of regulation; the relationship between decentralization/deconcentration; the responsibility of the State, public actors and public agents; and, finally, reflections on the concepts of territory and territoriality considering schooling, seeking to glimpse some possibilities within this scope.
Keywords: Schooling; Public education policies; Responsibility; Territoriality